An analytical presentation of the road safety situation in Mauritius – Policing experiences in the light of situational crime prevention (Belügyi Szemle, 2026)
Aim: The study aims to present the road safety situation and local policing responses in Mauritius through the theoretical framework of situational crime prevention. The research is based on the author’s data collection during a stay in Mauritius as a PhD student and police officer, as well as professional consultations with the Mauritius Police Force. Methodology: The analysis focuses on accident statistics from 2024–2025, the new penalty points system introduced in 2026, and criminologically relevant factors of the traffic environment. The study compares the island nation’s practices with international road safety trends. Findings: Although the total number of fatal accidents shows a 7.2% decrease, the victimization rate of pedestrians and especially the age group over 60 indicates a significant increase. The sanction system implemented in January 2026 and technology-based enforcement (Safe City) seek to manage environmental and human risks using the toolkit of situational crime prevention. Value: The study contributes to the interpretation of safety challenges in a specific traffic environment and offers findings relevant to international law enforcement knowledge exchange.